2012
DOI: 10.1016/j.transproceed.2012.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Proliferative Activity in Ischemia/Reperfusion Injury in Hepatectomized Mice: Effect of N-Acetylcysteine

Abstract: NAC preserved the remnant liver in mice and stimulates regeneration even after IR injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
(6 reference statements)
0
11
0
2
Order By: Relevance
“…This prompted us to determine whether oxidative stress could play a role in nuclear inclusion formation. N-acetyl cysteine is an antioxidant used to reduce oxidative stress both experimentally and clinically during acute liver injury [32]. When 9–10 month old HBsAg-Tg mice were treated with NAC, we observed a marked reduction in 4-HNE adduct formation ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…This prompted us to determine whether oxidative stress could play a role in nuclear inclusion formation. N-acetyl cysteine is an antioxidant used to reduce oxidative stress both experimentally and clinically during acute liver injury [32]. When 9–10 month old HBsAg-Tg mice were treated with NAC, we observed a marked reduction in 4-HNE adduct formation ( Fig.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, laboratory data have shown that NAC reduces the level of hepatic ROS and attenuate ROS‐induced liver injury after IRI . In addition to a reduction in lipid peroxidation, NAC also enhances regeneration of the liver and increases glutathione levels . Although tolerated well, there is still 3–6% anaphylactic reaction rate with intravenous use, that tends to resolve with either slowing or cessation of the infusion …”
Section: Discussionmentioning
confidence: 99%
“…Due to the results observed in liver transplantation studies, NAC has been subsequently used in patients undergoing major liver resection to prevent PHLF. Experimental studies have reported promising results on liver regeneration following the administration of NAC, and it is thought its mechanism of action is related to decreasing oxidative stress and the effects of IRI, in particular, in rats with a background of liver steatosis . Nevertheless, there is a lack of clinical data to support the use of NAC following liver resection.…”
Section: Introductionmentioning
confidence: 99%
“…One of the proposals found in the literature to lower or abolish the effects of oxidative stress is the exogenous addition of glutathione or its precursor, n-acetylcysteine 22,23 . A higher dose of such substances, even if controversial, may be beneficial because as the dose and duration of the treatment seems to be of value for reducing the damage involved in the ischemic tissue.…”
Section: Discussionmentioning
confidence: 99%